Analisis Motivasi Belajar Siswa terhadap Pembelajaran Matematika di Sekolah Menengah Atas - Baharsah, Nasrudin (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The purpose of this study was to determine students' learning motivation in mathematics learning in senior high schools. This study uses a quantitative method because the data processed is ratio data, and the focus of this study is to analyze students' learning motivation towards mathematics lessons at SMA Idhata Banjarmasin. The population in this study were students of SMA Idhata Banjarmasin. The sample used was class XI. The research instrument used a questionnaire containing statements with the aim of seeing students' learning motivation in mathematics subjects. Descriptive data analysis techniques to determine students' learning motivation from the results of the questionnaire data. The results of the study based on the Guttman scale showed that out of 24 students in class XI of SMA Idhata Banjarmasin, there were 22 students who had a